Improving Students Ability to Evaluate and Conclude Through A Scientific Approach - Syukri, Muhammad; Basri, Mahdalena; Halim, A.; Maghfirah, Siti (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
This study aims to improve students' assessment and inference skills through the application of the scientific approach. The research was conducted with a pre-experimental design using the single group pretest-posttest method. The study population involved 85 students of class XI of SMAN 1 Blangpegayon, and 22 students of class XI science 2 were selected as samples using purposive sampling. Essay tests on sound waves were used to assess students' critical thinking skills through pretest and posttest. Data were analyzed using N-Gain test and paired sample t test. The results showed that students' evaluation ability had an N-Gain value of 0.97, while the ability to conclude reached 0.99, both of which were classified as high. Hypothesis testing showed a significant difference between pretest and posttest scores with a value of 0.001 <0.05, based on the paired sample t test. Thus, it can be said that employing a scientific approach to the learning process can enchance the capacity to evaluate and conclude students